Energy Security in Algeria: Opportunities and Challenges - Mokrani, Mohamed Drif; Moudjari, Redouane (Finance and Business Economies Review, 2022)
Energy security has become one of the pillars of security concepts that have a scientific and practical dimension and one of the important variables that emerged in its status and role after the Cold War period. Energy security has become one of the important determinants that go into shaping the national security combination. We note that with the increasing pace of scientific and technological development and the advancement of industries, energy in its various forms has become an essential element in moving the wheels of international economies. The state authorities have come to attach the utmost importance to the issue of energy and the factors of the sustainability of its sources to ensure their energy security, and it has become clear that hydrocarbon-importing countries have a great dependence on exporting and producing countries